Valorização biotecnológica do glicerol residual do biodiesel para produção de biomassa e lipídeo unicelular (sco) por mucor circinelloides ucp 050 isolado de manguezal - Silva, Cinthya Barbosa da (2014)
Glycerol (also known as glycerin) is an important by-product in the process of manufacture of biodiesel, corresponding to 10% of the by-product formed in the reaction of transesterificação of this biofuel. The purification costs of raw glycerol is high and disables its use in the industries of foods, druggs, and cosmetics. Thus, several methods of reuse of residual glycerol have been attemped, including combustion, anaerobic digestion, animal food, as well as its biological conversion in products of aggregate value. Moreover, the establishment of a dynamics of related technological innovation and scientific development to the glycerin as a possible raw material for the microbial biotechnological processes are of great importance. In this study the effects of the residual glycerin of biodiesel were evaluated on the growth, biomass production, morphology, oxidative enzymes: superoxide dismutase; gluthation-S-Transferase and catalase, lipid peroxidation, production of lipids and fatty acid of Mucor circinelloides. The results revealed alterations in all parameters tested. The glycerin presence in culture medium induced increase in cellular growth and biomass compared to growth in glucose and pure glycerol. The residue metabolization is a viable alternative for exceeding glycerin produced for production of biomass, lipids and antioxidant enzymes, pointing the industrial and biotechnological potential application of the isolate. Moreover, the ability of use of the by-product also can be applied as substrate for biodiesel production.